2016
DOI: 10.1093/rheumatology/kew039
|View full text |Cite
|
Sign up to set email alerts
|

Marked underdiagnosis and undertreatment of hypertension and hypercholesterolaemia in rheumatoid arthritis

Abstract: The Dutch Trial Register, www.trialregister.nl, NTR3873.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 29 publications
1
36
0
1
Order By: Relevance
“…Related to the present findings, researchers from the Dutch Trial Registry recently found that RA patients were undertreated for both hyperlipidemia and hypertension due to no treatment or insufficient therapy to meet recommended target goals [26]. In contrast, more patients with RA are prescribed inhaled corticosteroids and antiasthma drugs than their non-RA counterparts, which may indirectly suggest a higher prevalence of obstructive lung disease as both lungs and pleura are common sites for extraarticular involvement in these patients [27].…”
Section: Discussionmentioning
confidence: 57%
“…Related to the present findings, researchers from the Dutch Trial Registry recently found that RA patients were undertreated for both hyperlipidemia and hypertension due to no treatment or insufficient therapy to meet recommended target goals [26]. In contrast, more patients with RA are prescribed inhaled corticosteroids and antiasthma drugs than their non-RA counterparts, which may indirectly suggest a higher prevalence of obstructive lung disease as both lungs and pleura are common sites for extraarticular involvement in these patients [27].…”
Section: Discussionmentioning
confidence: 57%
“…At present, available SDMARDs did not show any positive effect in controlling systemic blood pressure; on the contrary, NSAIDs and may rise the systemic blood pressure [23,26]. Furthermore, it must be pointed out that, as recently reported, SAH may not be optimally identified, in RA patients [27], thus contributing to the increase of CVEs risk.…”
Section: Discussionmentioning
confidence: 83%
“…Despite of the European League Against Rheumatism (EULAR) provided different sets of recommendations for the management of cardiovascular risk in inflammatory arthritis patients [18,19], cardiometabolic comorbidity remains still underdiagnosed and undertreated in RA patients [20]. Although these comorbidities are frequently occurring in RA patients, the evidence deriving from randomized clinical trials does not fully elucidate this topic.…”
Section: Introductionmentioning
confidence: 99%